Parental Involvement of Children with Special Needs: Insights from Epstein’s Six Domains Framework - Rejeki, Dewi Sri; Supratiwi, Mahardika; Widyastono, Herry; Gunarhadi, Gunarhadi; Hermawan, Hermawan; Yuwono, Joko; Cahyani, Leni Ambar (FKIP Universitas Lampung, 2025)
Abstract: Parental Involvement of Children with Special Needs: Insights from Epstein’s Six Domains Framework. Objectives: This study investigated the role of parents of children with disabilities in inclusive school settings. Methods: Employing a qualitative approach, data were collected through focus group discussions (FGD) to 17 parents for children with special needs and analyzed using ATLAS.ti software, following an interactive analysis model comprising data condensation, data presentation, and conclusion drawing/verification. Findings: Findings highlight the critical role parents play across six domains of involvement, as defined by Epstein's framework: creating supportive home environments (Parenting), engaging in clear communication with the school (Communicating), volunteering at the school (Volunteering), supporting learning at home (Learning at Home), participating in school-related decision-making (Decision-Making), and collaborating with the community to coordinate resources (Collaborating with the Community). These areas of involvement enable parents to actively contribute to inclusion in educational settings. Conclusion: This study underscores the importance of comprehensive parental engagement of children with disabilities within inclusive schools. Keywords: role of parents, disabilities, inclusive schools.